Improving Students’ TOEFL Listening Skills Through Online Learning During New Normal - Suharti Sirajuddin; Muhamad Yahrif (STAI Hubbulwathan Duri, 2023)
This research aimed to know the improvement of listening skills in TOEFL tests through online learning during the new normal. The focus of this research was to improve students' Listening skills for the TOEFL test. The materials of this research focused on TOEFL listening by using a combination of three online applications, namely Zoom, Edmodo, and WhatsApp. This research used a mixed-method design, quantitative and qualitative data collection. The samples involved 47 students of the English Education study program at Megarezky University by using purposive random sampling. Pre and Post-test result, observation, and open-ended questions are used to collect data. Pre and post-test results of students were analyzed by using the T-test of the SPSS 20 version. Open-ended questions and observation are used as additional data from SPSS analysis. The results of this study showed that a mean score of 16.4 on pre-tests improved compared with a 33.5 mean score on the post-test. Based on students' open-ended questions, students wrote positively about the online learning process and claimed that it helped them to increase their skills in listening. Using several methods to optimized online learning during the new normal is essential, especially for improving students listening skills.